Evaluation of the Professional Competency of University Faculty Members as Perceived by Higher Education Students - Ibad, Fareeda; Muhammad Yousuf Sharjeel (Journal of Education and Educational Development, 2021)
This study considered the importance of professionalism in university faculty performance since effective learning has its basis the superior instructional and professional competence of teachers. The purpose of the study was to attempt to suggest a hybrid model of faculty effectiveness evaluation based on the perceptions of higher education students regarding their faculty’s quality of teaching. The research focused on involving higher education students in determining the effectiveness characteristics of their teachers in order to provide a justification for developing effective operational systems for teacher evaluation in Pakistan. The study used a mixed methods research design comprising both quantitative and qualitative methods for the purpose of data collection and analysis.  To address the research problem, the researcher chose to base the theoretical framework for the research on Marsh’s (1982) research and development of the Student Evaluation of Educational Quality (SEEQ) questionnaire. Further to this, the researcher developed the conceptual framework through the research of Gurney and Wise (2002) from where the criteria for evaluating the effective teacher questionnaire emerged having characteristics similar to those in the SEEQ and was used to attempt to bridge the time gap and establish the validity of the SEEQ over more than three decades. The data was gleaned from using both questionnaires from a sample of n= 395 under two-tailed probability distribution. All constructs’ reliability was above the criteria suggested by different scholars rendering the SEEQ questionnaire as reliable for the study.